Mathematical Modeling as a Didactic Strategy for Calculus Teaching - Molina-Mora, Jose Arturo (2017)
Mathematical modeling is the activity that represents, manipulates, and communicates real-world objects with mathematical content; it also allows the simulation of complex processes, generates hypotheses, and suggests experiments or validation methods. Mathematical modeling is presented as a teaching strategy to simulate and interpret different real or academic life problems and situations by demonstrating different application conditions of university mathematical course contents. Specifically, in Calculus II, the strategy seeks to address the need to show and manipulate contents applications of improper integrals, series and Taylor polynomials, polar coordinates, and conic sections on specific problems with examples in biological sciences and engineering areas. This implementation respond to a paradigm that seeks innovation and continuous improvement of teaching and learning processes which is pertinent because of the existence of a platform incorporating ICTs (Information and Communications Technology) in Calculus II, and favoring the use of specialized software for the creation and manipulation of mathematical models.